Clinical Implications of Urinary C-Peptide Creatinine Ratio in Patients with Different Types of Diabetes. (7th August 2019) - Wang, Yanai; Gao, Ying; Cai, Xiaoling; Chen, Ling; Zhou, Lingli; Ma, Yumin; Gong, Siqian; Han, Xueyao; Ji, Linong
Abstract : Introduction . Urinary C-peptide creatinine ratio (UCPCR) is used as a marker of endogenous insulin secretion. This study aims to assess the effectiveness of UCPCR for distinguishing between type 1 diabetes (T1DM) and non-T1DM (monogenic diabetes and T2DM) and predicting therapeutic choices in type 2 diabetes (T2DM) patients. Methods . Twenty-three patients with genetically confirmed monogenic diabetes (median age 35.0 years (interquartile range 30.0-47.0), 13 (56.5%) men), 56 patients with T1DM (median age 46.0 years (interquartile range 26.5-59.5), 28 (50.0%) men), 136 patients with T2DM (median age 53.0 years (interquartile range 42.0-60.0), 87 (64.0%) men), and 59 healthy subjects (median age 36.0 years (30.0-42.0), 26 (44.1%) men) were included. UCPCR was collected in the morning. Receiver operating characteristic (ROC) curves were used to identify optimal UCPCR cut-off values to differentiate T1DM from non-T1DM. This UCPCR cut-off was used to divide T2DM patients into two groups, and the two groups were compared. Results . The UCPCR was lower in patients with T1DM compared with T2DM, monogenic diabetes, and healthy subjects, while the UCPCR was similar in T2DM and monogenic diabetes. A UCPCR cut-off of ≥0.21 nmol/mmol distinguished between monogenic diabetes and T1DM (area under the curve [AUC], 0.949) with 87% sensitivity and 93% specificity.UCPCR ≥ 0.20   nmol / mmol had 82% sensitivity and 93% specificity for distinguishing between T2DM and T1DM, with an AUC of 0.932. UCPCR was not reliable for distinguishing between monogenic diabetes and T2DM (AUC, 0.605). Twenty-five of 136 (18.4%) T2DM patients hadUCPCR ≤ 0.20   nmol / mmol . Compared with T2DM patients with aUCPCR > 0.20   nmol / mmol, T2DM patients withUCPCR ≤ 0.20   nmol / mmol had a lower serum C-peptide (fasting C-peptide, 0.39 nmol/L vs. 0.66 nmol/L, P < 0.001 ; postprandial C-peptide, 0.93 nmol/L vs. 1.55 nmol/L, P < 0.001 ), lower BMI (22.8 kg/m 2 vs. 25.2 kg/m 2, P = 0.006 ), and higher percentage of insulin or secretagogue therapy (92.0% vs. 59.5%, P = 0.002 ). Conclusions . UCPCR is a practical and noninvasive marker that can distinguish between TIDM and T2DM or monogenic diabetes.UCPCR ≤ 0.20   nmol / mmol reflects severe impaired beta cell function and the need for insulin or secretagogue therapy in T2DM patients.